The Reformation of Pesantren Education System: The Study on Abdul Wahid Hasyim Thoughts the Perspective of Islamic Education Philosophy - Maragustam (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
Islamic educational orientation of AWH life in the middle of the twentieth century is purely religious. While AWH already initiated educational reform for Pesantren (boarding schools) oriented on ideal hereafter and mundane pragmatic. Islamic education which was formerly monopolized by traditional educational institutions and the students who could not think freely were reviewed by AWH through encouraging his students to think more openly and free yet carry on proper obedient to the teachers. The analysis was conducted through data reduction, display, and data verification. According to AWH, human is perfect being consists of physical and spiritual components and homo educandus capable of thinking, feeling and reasoning spiritually. The perfectness can be achieved through education by developing the potential and thinking skills, physical skills strengthened by faith. Pesantren educational reformations are (1) the foundation of pesantren education are Ilahiyah verses (Al-Qur’an and Sunnah) and kauniyah (the evidence of God’s existence appeared in natural laws, the system of universe); (2) The purpose of pesantren education is to shape human to be virtuous being accompanied with developed thinking skills, piety to Allah, and equipped with life skills. This, is actually in accordance with contemporary educational thought which covers cognitive, affective, spiritual and psychomotor aspects; (3) the curriculum of pesantren education should balance between practical life and ideal life, that is between religious sciences and secular sciences; (4) the teaching methods applied in pesantren are traditional methods such as sorogan and bandongan, as well as modern methods such as experiment, tutorial, and mudzakarah (discussions nad seminars); (5) learning resources such as library constitutes the heart of scientific life in pesantren, which was distinctively remarkable in AWH’s era. Factors influencing AWH’s thoughts are his own personal learning, the burgeoning thoughts proliferating during his era, social-cultural environment, educational background, his own intelligence, and support from policy makers, particularly his own family.